2020
DOI: 10.1007/s40267-020-00737-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and preventive practices related to COVID-19: a cross-sectional study in two Pakistani university populations

Abstract: Objective The aim of this study was to assess COVID-19-related knowledge, attitudes, and preventive practices of two Pakistani university populations. Methods A cross-sectional study was conducted among students and employees of two higher education institutions in Lahore, Pakistan, namely the University of Lahore and the Gulab Devi Educational Complex. Participants were recruited using a convenient sampling method. A validated 45-item, self-administered questionnaire was used to collect data. Total possible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
135
16
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(218 citation statements)
references
References 14 publications
38
135
16
29
Order By: Relevance
“…This may also identify if there is a greater need for interventions in one of the behaviours or particular activities within a behaviour. Participants reported increased handwashing (88%) during the pandemic as has been found in other studies of university students [22,23,48,49], and this exceeded increases in a general population in Australia during the initial stages of the COVID-19 pandemic [52] or the UK H1N1 outbreak [28]. Both the latter UK survey and this survey occurred after major government advertising campaigns, including lea et drops, suggesting that in the current environment, the government information campaign has been particularly effective, as was also found in South Korea during the H1N1 pandemic [22].…”
Section: Investigation Of Knowledge/socio-cognitive Perception Towardsupporting
confidence: 76%
See 4 more Smart Citations
“…This may also identify if there is a greater need for interventions in one of the behaviours or particular activities within a behaviour. Participants reported increased handwashing (88%) during the pandemic as has been found in other studies of university students [22,23,48,49], and this exceeded increases in a general population in Australia during the initial stages of the COVID-19 pandemic [52] or the UK H1N1 outbreak [28]. Both the latter UK survey and this survey occurred after major government advertising campaigns, including lea et drops, suggesting that in the current environment, the government information campaign has been particularly effective, as was also found in South Korea during the H1N1 pandemic [22].…”
Section: Investigation Of Knowledge/socio-cognitive Perception Towardsupporting
confidence: 76%
“…However, there was only a moderate level of consistent ("Mostly" or Always") practice across all 8 hand hygiene activities (42.0%). While differences in the questions may affect comparability to other studies, this is still well within the wide range found in other studies, looking at handwashing alone or a broader range of hygiene behaviours [28,49,[56][57][58]. Others have also found that speci c hand hygiene behaviours such as face /mouth/nose touching may be particularly di cult [20].…”
Section: Investigation Of Knowledge/socio-cognitive Perception Towardmentioning
confidence: 59%
See 3 more Smart Citations